COVID-19 POEMS AS CULTURAL RESPONSE TO PANDEMIC IN INDONESIA - Alhadar, Fachmi; Amin, Safrudin (Jurnal Adabiyah, 2021)
Covid-19 has shocked entire world in almost all aspects of social and individual life. It appears that this pandemic has threaten individual and public health, infused political concerns between and within countries, and caused economic downturn. Studies on response to the pandemic have covered wide ranges of issues such as policies, psychological, economic, education etc.  This article is interested in exploring how people response to this pandemic through the use of their cultural stocks, particularly the use of poetry. In so doing, this article samples two poems written government public figures. The poems are Corona Virus written by M. Jusuf Kalla, a former vice president of Indonesia, and Corona Virus Disease 2019 written by Sri Purnomo, the Regent of Sleman Yogyakarta, and analyses their contents. This study uses netnography method in collecting data and makes use of qualitative text analysis, particularly qualitative content analysis, in analyzing the available data. By using anthropological approach, this study interprets the interpretations of the pandemic via digging the content of their poems. This study found that interpretations of the pandemic expressed through poems focused on several main themes and that these themes were strongly shaped by their cultural values and beliefs. In other words, their poems are not a mere personal expression but also cultural responses to the covid-19 pandemic.Keywords: Covid-19; Pandemic; Response; Poem; Culture.الملخصلقد صدم Covid-19 العالم بأسره في كل جانب من جوانب الحياة الاجتماعية والفردية تقريبًا. يبدو أن هذا الوباء قد هدد صحة الأفراد والمجتمعات ، وأثار مخاوف سياسية بين البلدان وداخلها ، وتسبب في انكماش اقتصادي. غطت الدراسات حول الاستجابة للوباء قضايا مختلفة مثل السياسة وعلم النفس والاقتصاد والتعليم وغيرها. تهتم هذه المقالة باستكشاف كيفية استجابة المجتمع لهذا الوباء من خلال استخدام مخزونهم الثقافي ، وخاصة استخدام الشعر. وهكذا ، يأخذ هذا المقال عينة من قصيدتين كتبها شخصيتان حكوميتان. القصائد هي فيروس كورونا كتبها م. تستخدم هذه الدراسة طريقة netnographic في جمع البيانات وتستخدم التحليل النوعي للنص ، وخاصة تحليل المحتوى النوعي ، في تحليل البيانات المتاحة. باستخدام نهج أنثروبولوجي ، تفسر هذه الدراسة تفسير الوباء من خلال استخراج محتويات شعرهم. ووجدت الدراسة أن تفسيرات الوباء المعبر عنها من خلال الشعر تركز على عدة مواضيع رئيسية وأن هذه الموضوعات تشكلت بقوة من خلال قيمهم الثقافية ومعتقداتهم. وبعبارة أخرى ، فإن قصائدهم ليست مجرد تعبير شخصي ، بل هي أيضًا استجابة ثقافية لوباء COVID-19.الكلمات المفتاحية: Covid-19؛ جائحة؛ إجابة؛ شعر؛ حضاره.ABSTRAKCovid-19 telah mengejutkan seluruh dunia dihampir semua aspek kehidupan sosial dan individu. Tampaknya pandemi ini telah mengancam kesehatan individu dan masyarakat, menimbulkan kekhawatiran politik di antara dan di dalam negara, dan menyebabkan kemerosotan ekonomi. Kajian tentang respons terhadap pandemi telah mencakup berbagai isu seperti kebijakan, psikologis, ekonomi, pendidikan dan lain-lain. Artikel ini tertarik untuk mengeksplorasi bagaimana respons masyarakat terhadap pandemi ini melalui penggunaan stok budaya mereka, khususnya penggunaan puisi. Dengan demikian, artikel ini mengambil sampel dua puisi yang ditulis oleh dua tokoh publik pemerintah. Puisi tersebut adalah Corona Virus ditulis oleh M. Jusuf Kalla, seorang mantan wakil presiden Indonesia, dan Corona Virus Disease 2019 yang ditulis oleh Sri Purnomo, bupati Sleman Yogyakarta, dan menganalisis isinya. Penelitian ini menggunakan metode netnografi dalam mengumpulkan data dan menggunakan analisis teks kualitatif, khususnya analisis isi kualitatif, dalam menganalisis data yang tersedia. Dengan menggunakan pendekatan antropologi, penelitian ini memaknai interpretasi pandemi melalui penggalian isi puisi mereka. Studi ini menemukan bahwa interpretasi pandemi yang diungkapkan melalui puisi berfokus pada beberapa tema utama dan bahwa tema-tema ini sangat dibentuk oleh nilai-nilai budaya dan kepercayaan mereka. Dengan kata lain, puisi-puisi mereka bukan sekadar ekspresi pribadi tetapi juga respons budaya terhadap pandemi covid-19.